KOMUNITAS FUNGI RIZOSFER PADI LOKAL ASAL BANTEN - Pratiwi, Novia Nur; Khastini, Rida Oktorida; Lestari, Iing Dwi; Maryani, Nani (Leuit (Journal of Local Food Security), 2021)
The rhizosphere is a part of the soil located around the plant roots. The community of microorganisms in the rhizosphere is more diverse than the non-rhizosphere soil. Fungi are the most common microorganisms found in the rhizosphere and could influence soil fertility and increase plant resistance against pathogen and environmental stress. This research aimed to study the community of fungi in the rhizosphere of local rice varieties from Banten. Samples were collected from the rhizosphere of eight local rice varieties of Banten, i.e. padi Kewal Bulu Hideung, padi Limar, padi Guling, padi Siang, padi Cokrom, ketan Langgasari, ketan Ruyung dan ketan Cae. Fungi were isolated using the serial dilution method and plated into Potato Dextrose Agar medium. The fungal isolates recovered from the medium were purified using the same medium. Fungal isolates were identified based on their morphological characters. In total, 35 isolates were recovered belonging to seven genera, namely Aspergillus, Chaetomium, Fusarium, Gongronella, Mucor, Penicillium, and Trichoderma. The most abundant fungal community was found in the rhizosphere of padi Guling and padi Ruyung. This research gives insight into the diversity of fungal rhizosphere of local rice from Banten, which might have a role in their resistance against pathogens. Testing these isolates against the particular pathogen of rice could be done in the future to see the potentials for biological control used in rice.